A Regional Health Care Network: eHealth.Braunschweig - Gusew, N.; Bartkiewicz, T.; Bautsch, W.; Gerlach, A.; Goldapp, M.; Haux, R.; Heller, U.; Kierdorf, H. P.; Kleinschmidt, T.; Ludwig, W.; Markurth, U.; Pfingsten-Würzburg, S.; Plischke, M.; Reilmann, H.; Schubert, R.; Seidel, C.; Warnke, R. (Methods of Information in Medicine, 2012)
Background: Health care network eHealth.Braunschweig has been started in the South-East region of Lower Saxony in Germany in 2009. It composes major health care players, participants from research institutions and important local industry partners.Objectives: The objective of this paper is firstly to describe the relevant regional characteristics and distinctions of the eHealth.Braunschweig health care network and to inform about the goals and structure of eHealth.Braunschweig; secondly to picture and discuss the main concepts and domain fields which are addressed in the health care network; and finally to discuss the architectural challenges of eHealth.Braunschweig regarding the addressed domain fields and defined requirements.Methods: Based on respective literature and former conducted projects we discuss the project structure and goals of eHealth.Braunschweig, depict major domain fields and requirements gained in workshops with participants and discuss the architectural challenges as well as the architectural approach of eHealth.Braunschweig network.Results: The regional healthcare network eHealth.Braunschweig has been established in April 2009. Since then the network has grown constantly and a sufficient progress in network activities has been achieved. The main domain fields have been specified in different workshops with network participants and an architectural realization approach for the transinstitutional information system architecture in the healthcare network has been developed. However, the effects on quality of information processing and quality of patient care have not been proved yet. Systematic evaluation studies have to be done in future in order to investigate the impact of information and communication technology on the quality of information processing and the quality of patient care.Conclusions: In general, the aspects described in this paper are expected to contribute to a systematic approach for the establishment of regional health care networks with lasting and sustainable effects on patient-centered health care in a regional context.
Keywords: Regional health care networks; patient-centered care; integrated health care systems; intersectoral communication.